How to identify relevant product properties in the context of user-product interaction? - Schröppel, Tina; Miehling, Jörg; Wartzack, Sandro (Procedia CIRP, 2020)
A smooth and pleasurable user-product interaction (UPI) forms the basis of a successful user-centred design. An essential part of achieving this is the consideration of the ‘right’ product properties whose identification currently requires huge monetary, temporal and personnel effort. This contribution presents a more sufficient approach for identifying relevant product properties in the context of UPI as well as its first evaluation. To identify relevant properties, the UPI is first described by standard interactions which are secondly used as input for searching a knowledge base. For the initial evaluation an application example (percussing drill) is conducted. It shows that the outcome of the approach is indeed plausible but usability should be improved. Future research focuses on a deeper evaluation and improvements regarding accessibility and traceability.<br
Keywords: user-centred design; user-product interaction; product properties; relevance; evaluation; user-satisfaction; user experience; usability